To solve the expression, we need to simplify the given expression using the order of operations (PEMDAS).
−5 + 34(8h + 12) − 10h
First, we can simplify the terms inside the parentheses:
= −5 + 34 * 8h + 34 * 12 − 10h
Next, we can apply the distributive property to multiply each term inside the parentheses by 34:
= −5 + 272h + 408 − 10h
Combining like terms:
= (272h - 10h) + (-5 + 408)
= 262h + 403
Therefore, the simplified expression is 262h + 403.
−5+34(8h+12)−10h
7 answers
−5+3/4(8h+12)−10h
To solve the expression, we need to simplify the given expression using the order of operations (PEMDAS).
−5 + (3/4)(8h + 12) − 10h
First, we can simplify the terms inside the parentheses:
= −5 + (3/4) * 8h + (3/4) * 12 − 10h
Next, we can apply the distributive property to multiply each term inside the parentheses by 3/4:
= −5 + (3/4)(8h) + (3/4)(12) − 10h
= −5 + (24h/4) + (36/4) − 10h
= −5 + 6h + 9 − 10h
Combine like terms:
= (-5 + 9) + (6h - 10h)
= 4 - 4h
Therefore, the simplified expression is 4 - 4h.
−5 + (3/4)(8h + 12) − 10h
First, we can simplify the terms inside the parentheses:
= −5 + (3/4) * 8h + (3/4) * 12 − 10h
Next, we can apply the distributive property to multiply each term inside the parentheses by 3/4:
= −5 + (3/4)(8h) + (3/4)(12) − 10h
= −5 + (24h/4) + (36/4) − 10h
= −5 + 6h + 9 − 10h
Combine like terms:
= (-5 + 9) + (6h - 10h)
= 4 - 4h
Therefore, the simplified expression is 4 - 4h.
Are you sure
Apologies for the mistake. Let's revise the solution.
−5 + 3/4(8h + 12) − 10h
First, we can simplify the terms inside the parentheses:
= −5 + 3/4 * 8h + 3/4 * 12 − 10h
Next, we can apply the distributive property to multiply each term inside the parentheses by 3/4:
= −5 + (3/4)(8h) + (3/4)(12) − 10h
= −5 + (24h/4) + (36/4) − 10h
= −5 + 6h + 9 − 10h
Combine like terms:
= (-5 + 9) + (6h - 10h)
= 4 - 4h
Therefore, the simplified expression is 4 - 4h.
−5 + 3/4(8h + 12) − 10h
First, we can simplify the terms inside the parentheses:
= −5 + 3/4 * 8h + 3/4 * 12 − 10h
Next, we can apply the distributive property to multiply each term inside the parentheses by 3/4:
= −5 + (3/4)(8h) + (3/4)(12) − 10h
= −5 + (24h/4) + (36/4) − 10h
= −5 + 6h + 9 − 10h
Combine like terms:
= (-5 + 9) + (6h - 10h)
= 4 - 4h
Therefore, the simplified expression is 4 - 4h.
-5 + 3/4(8h+12) -10h
To solve the expression, we need to simplify the given expression using the order of operations (PEMDAS).
-5 + 3/4(8h + 12) - 10h
First, we can simplify the terms inside the parentheses:
= -5 + 3/4 * 8h + 3/4 * 12 - 10h
Next, we can apply the distributive property to multiply each term inside the parentheses by 3/4:
= -5 + (3/4)(8h) + (3/4)(12) - 10h
= -5 + (24h/4) + (36/4) - 10h
Now, we can simplify the fractions:
= -5 + 6h + 9 - 10h
Next, we combine like terms:
= (6h - 10h) + (-5 + 9)
= -4h + 4
Therefore, the simplified expression is -4h + 4.
-5 + 3/4(8h + 12) - 10h
First, we can simplify the terms inside the parentheses:
= -5 + 3/4 * 8h + 3/4 * 12 - 10h
Next, we can apply the distributive property to multiply each term inside the parentheses by 3/4:
= -5 + (3/4)(8h) + (3/4)(12) - 10h
= -5 + (24h/4) + (36/4) - 10h
Now, we can simplify the fractions:
= -5 + 6h + 9 - 10h
Next, we combine like terms:
= (6h - 10h) + (-5 + 9)
= -4h + 4
Therefore, the simplified expression is -4h + 4.